2015
DOI: 10.2147/hmer.s89447
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokine gene polymorphisms with hepatitis C virus infection in a population from Rio de Janeiro, Brazil

Abstract: BackgroundThe host immune response is an important indicator of the outcome of hepatitis C virus (HCV) infection and disease progression. The aim of this study was to explore cytokine gene polymorphisms as a candidate for susceptibility to persistent HCV infection or HCV spontaneous clearance in a population from Rio de Janeiro, Brazil.MethodsGenetic polymorphisms in the cytokines, tumor necrosis factor-alpha (−308), transforming growth factor-beta 1 (codons 10 and 25), interleukin-10 (IL-10; −1082 and −592), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Several studies have reported the distribution of the rs12979860 genotypes in different populations, mainly assessing its correlation with the susceptibility to different viral infections and response to antiviral treatments (Wu et al, 2012;Porto et al, 2015;Taheri et al, 2015;Echeverría et al, 2018). The correlation of this distribution and the local ancestry of these populations as well as its implications have also been assessed (Indolfi et al, 2014b;Rizzo et al, 2016), though this is the first report in an Argentinean global population.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Several studies have reported the distribution of the rs12979860 genotypes in different populations, mainly assessing its correlation with the susceptibility to different viral infections and response to antiviral treatments (Wu et al, 2012;Porto et al, 2015;Taheri et al, 2015;Echeverría et al, 2018). The correlation of this distribution and the local ancestry of these populations as well as its implications have also been assessed (Indolfi et al, 2014b;Rizzo et al, 2016), though this is the first report in an Argentinean global population.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…[ 19 ] Fabrício-Silva et al also carried out a study among 221 Brazilian HCV patients, including 184 patients infected with genotype 1 and 37 patients infected with genotype 2. [ 20 ] They concluded that IL-28B gene polymorphism (rs12979860 and rs12980275) can predict spontaneous HCV clearance rate and SVR rate, and IL-6 (rs1800795) G allele was involved in increased inflammation scores. Similarly, a meta-analysis indicated that patients carrying G allele of IL-6 (rs1800795) may be more likely to suffer from liver diseases, which was ethnic-dependent.…”
Section: Discussionmentioning
confidence: 99%